The influence of locally elected officials among Sangguniang Kabataan leaders in Mandurriao, Iloilo City. - Panagdato, Denny J. II; Turingan, Ryby Anna F. (2003.)
This research paper looks into the influence of barangay officials among Sangguniang Kabataan officers in 11 baranagays randomly selected in Mandurriao IloiloCity. Using survey questionnaires, this study looked at which level (planning, decision-making and implementation) barangay officials influence is felt. To answer such inquiry, the study has three objectives namely: (1) to know whether barangay officials influence the decision making of Sangguniang Kabataan leaders; (2) to identify the manifestations of influence of barangay officials among Sangguniang Kabataan leaders; (3) to identify at which stage influence lie, whether at planning, decision-making or implementation. Influence in this study is limited only to three categories of SK decision-making process. The major findings of this study suggst that barangay officials have indirect influence among SK officers and this is felt at the planning stage - through the participation of barangay officials in decision-making of SK by giving suggestion and comments during SK sessions, and in the implementation stage - through the oversight measures set by the barangay officials.
Research Paper (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Sangguniang Kabataan -- Manduriao, Iloilo